Giuseppe Dessí Storia e catalogo di un archivio - Landini, Agnese (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2002)
Twenty-five years after the death of one of the most refined and secluded writers of the second half of the 20th century, the complete catalogue of works and author papers in the Giuseppe Dessí Collection is available, thanks to the work and philological expertise of Agnese Landini. The filing of the material, deposited in the Contemporary Archives of the Gabinetto Vieusseux in Florence, allows to retrace the complete bibliography of the published and unpublished works of the Sardinian writer and, while telling the story of a narrative path through documents, it eases access to notes and drafts of novels, short stories, plays, anthologies, translations, essays, poems, interviews.